1998
DOI: 10.1094/pdis.1998.82.5.496
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Basis and Monitoring of Resistance of Botryotinia fuckeliana to Anilinopyrimidines

Abstract: The anilinopyrimidines constitute a new class of mainly protective, broad-spectrum fungicides with a high activity against Botryotinia fuckeliana, the causal agent of gray mold on a wide range of host plants. The present study was initiated to investigate the genetic basis of resistance to anilinopyrimidines in B. fuckeliana and to assess the frequency of resistant isolates in vineyards in Switzerland exposed to experimental applications of anilinopyrimidines. In mating experiments, two sensitive reference iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 15 publications
1
34
0
Order By: Relevance
“…Furthermore, it was noted that moderate sensi-tivity of T. harzianum to cyprodinil and fludioxonil is due to active ingredients of two different families with two different modes of actions [20]. In addition, T. harzianum (Jn14) was almost insensitive to Pyrimethanil.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was noted that moderate sensi-tivity of T. harzianum to cyprodinil and fludioxonil is due to active ingredients of two different families with two different modes of actions [20]. In addition, T. harzianum (Jn14) was almost insensitive to Pyrimethanil.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic analysis of laboratory mutants of B. cinerea resistant to the phenylpyrrole fungicide CGA 173506 showed that, in most mutants, resistance was caused by a single gene (Faretra & Pollastro, 1993b). Recently, Hilber & Hilber-Bodmer (1998) demonstrated that resistance to the anilinopyrimidine fungicide cyprodinil segregated in a 1 : 1 ratio and is therefore probably monogenic.…”
Section: Introductionmentioning
confidence: 99%
“…One of the first studies ) that screened multiple fungicide resistances in B. cinerea found resistance to anilopyrimidines (AP, e.g. cyprodinil, mepanipyrim, pyrimethanil) and identified two distinct resistance phenotypes: The most AP-resistant isolates were resistant to only anilinopyrimidines, suggesting action on the hitherto unidentified, single target gene (Hilber and Hilber-Bodmer 1998) and a second phenotype that included resistance to distinctly different classes of fungicides including dicarboximides, phenylpyrroles, sterol biosynthesis inhibitors (e.g. tolfanate, prochloraz, tebuconazole) and the hydroxyanilide derivative, fenhexamid, consistent with an MDR phenotype.…”
Section: Mdr-efflux Pumps and Resistancementioning
confidence: 99%